Pengaruh Atribut Produk Wisata Terhadap Kepuasan Wisatawan - Rahayu, Agus (Jurnal Trikonomika, 2010)
Development of distro and clothing production is relevant to attributes of shopping tourism products and the number of tourist who visit Bandung. Negative effects such as traffic congestion, criminal acts, and the like may emerge and hamper efforts to improve the city image or visitorsâsatisfaction. If this unfavourable situation happened, the existence of distro and clothing shopping tourism or the city of Bandung as a Shopping Tourist Destination would be threatened. Research method in use was a descriptive and explanatory survey, and the samples were domestic tourist who visited Bandung. The targeted population was domestic tourist from Jakarta and the sample size was 100. The variables comprised attributes of shopping tourism (destination attraction, destination facilities and services, destination accessibility, destination image, and prices), and the satisfaction of tourist shoppers. Data were collected by a questionnaire and analyzed by a path analysis technique.Finding show that the visitors or tourists who visited Bandung provided different responses to the attributes of distro and clothing products. They geve more positive responses to destination attractions than any other attributes. Their visit and/or shopping satisfaction was generally mediocre, as indicated by 0.69 average satisfaction index. As a whole, distro and clothing product attributes led to 80.20 per cent of visitorsâ satisfaction. Destination attractions had a more dominant effect on the visitorsâ satisfaction that any other attributes.